ANALISIS LAJU JUMLAH PENDUDUK TERHADAP KETERSEDIAAN AIR BERSIH UNTUK PEMENUHAN KEBUTUHAN RUMAH TANGGA DI DESA LAKAT KECAMATAN KUATNANA KABUPATEN TIMOR TENGAH SELATAN - Maro, Ruth Salomi; Samin, Mikael; Pamungkas, Bella Theo Tomi (Universitas Nusa Cendana, 2023)
The problem of this research is how the availability of clean water to fulfill household needs in Lakat Village and whether the number of population affects the need for clean water in Lakat village. The aim is to find out the availability of clean water to meet household needs in Lakat village and the number people who influence the need for clean water in Lakat village. This research method is quantitative descriptive, with a sample of 37 families, data collection techniques namely observation, quistionnaires and documentation studies. The data used in this study is the variabel availability of clean water to fulfill houshold needs and the projected population for the next 5 years. The research was conducted in the village of lakat, sub-distric of kuatnana, south central timor regency, the village lacks clean water with the result showing the based on the result of the variabel availaibility of clean water for meeting household needs, namely the higher the population , the higher the demand for red water is increasing, namely by using prectange with criteria |>50% qualified with the number of item 17 , while < 50% with the number of item 5 did not meet requirements for population projections for the next 5 years as much 2.374 poeple with clean water needs of 1,23 liter second . Based on the results of the research above, it can be concluded that in this study the more the population increases, the more the water needs will also increases.